A STUDY ON THE PREVALENCE, ASSOCIATED FACTORS, AND PREGNANCY OUTCOMES OF WOMEN WITH SLEEP DISORDERS IN THE THIRD TRIMESTER AND POSTPARTUM AT CANTHO CITY OBSTETRICS AND GYNECOLOGY HOSPITAL, 2024–2026 (Vietnam Journal of Community Medicine, 2026)
Background: Sleep disorders during pregnancy are a significant concern due to their effects on maternal health, fetal development, and postpartum recovery.Objectives: To determine the prevalence, associated factors, and pregnancy outcomes of women with sleep disorders during the third trimester and postpartum period at Can Tho City Obstetrics and Gynecology Hospital.Methods: A cross-sectional study was conducted on 380 women in the third trimester (28–41 + 6 weeks) who delivered and received postpartum care at the hospital. Sleep quality was assessed using the Pittsburgh Sleep Quality Index (PSQI > 5 indicating sleep disorder). Data were analyzed with SPSS 20.0 using descriptive statistics, χ² tests, and multivariable logistic regression (p ≤ 0.05 considered significant).Results: The prevalence of sleep disorders was 61.8% during the third trimester and 74.2% postpartum. Nine factors were significantly associated: parity, medical or pregnancy complications, pregnancy intention, maternal self-confidence, body image pressure, occupational stress, spousal support, husband’s smoking, and alcohol use (p  0.05), indicating no statistically significant difference.Conclusion: Sleep disorders are common among women in late pregnancy and increase postpartum. Although no significant association was found between sleep disorders and delivery outcomes, early screening and psychosocial support are essential to enhance maternal well-being and postpartum recovery.
Keywords: sleep disorders, pregnant women, third trimester of pregnancy, postpartum period.